Accounting for the effects of entrepreneurial orientation on SMEs' job creation capabilities: A social capital and self-determination perspective - Ademilua, Victoria A.; Lasisi, Taiwo T.; Ogunmokun, Oluwatobi A.; Ikhide, Juliet E. (Wiley, 2022)
Hinged on the tenets of both social capital and self-determination theories, this study is designed to unravel the impact of entrepreneurial orientation of cooperative societies in job creation and small and medium-sized enterprise (SME) performance. Research into cooperative societies and entrepreneurial orientation in SMEs is burgeoning, yet our understanding of the mechanism of operation or impact between cooperative membership and performance remains unclear. Given the lack of empirical research on the role of cooperative society's membership and entrepreneurial orientation on performance in the SMEs, especially in an African context, the current study addresses the relationships between cooperative society, entrepreneurial orientation, job creation, and business performance in the Nigerian SMEs. Data were generated from 500 Nigerian businesses and the results were analyzed using hierarchical multiple regression. Results confirm the study hypotheses. Implications for management are discussed, along with suggestions for further research.
Keywords: Strategic Orientations; Dynamic Capabilities; Market Orientation; Performance